Some Microhistological Changes In Superior Colliculus Following Chronic Intake Of Aqueous Neem Leaves Extract In Adult Wistar Rats (Rattus Norvegicus) - FAKUNLE P.B; AJIBADE A.J (International Journal of Pharma and Bio Sciences, 2012)
The plant, Azadirachta indica A Juss, family Meliaceae that is commonly used for the traditional treatment of malaria and other associated conditions in form of decoction, in which unspecified quantities are usually consumed without due regards to toxicological and other adverse effects .The present study was designed to investigate some effects of chronic Azadirachta indica (Neem) leaf extract on the microarchitecture of the visual relay center superior colliculus of adult wistar rats the relationship of which scanty literature is available as at present. Forty adult wistar rats both sexes of average weight 190±21.6g were randomly distributed after acclimatization into 4 groups (n=10) T1,T2, T3 and C such that rats in groups T1,T2 and T3 were given 400mg/Kg.B.wt,300mg/Kg.B.wt and 200mg/Kg.B.wt of aqueous neem extract while group C (control) received distilled water all for 14 days after which the rats were sacrificed by whole body intracardiac perfusion fixation and processed for routine histological techniques.The respective slides were then stained for Nissls substance. Statistical analysis showed insignificantly decreased P<0.05 weight (mean± sem, 202.4±28.3,207±9.6&213± 3.24) g in groups T1, T2 and T3 respectively compared to the control group with mean± sem, 217.4±7.3g. Significantly reduced neuronal density (P>0.05) of 44% and 38% neuronal loss in treatment groups T1 and T2 compared to control group was recorded. Histological findings showed distorted pyramidal neurons with scanty distribution of glial cells more marked in group T1 but less pronounced in group T2 while sections in T3 and Control groups appear normal. These alterations may affect normal functionality of superior colliculus most especially in the maintenance of saccade